Safe Nurse Staffing is More than Numbers and Ratios. Issue 5 (September 2017) - Simpson, Kathleen Rice
Abstract : Safe staffing is not numbers or ratios, rather the essential nursing care for optimal outcomes. Productivity targets should financially support enough nurses to provide care that is required based on national standards and guidelines. The numbers recommended in the AWHONN (2010) staffing guidelines represent the ability to perform that requisite nursing care.